AtHB2, a class II HD‐ZIP protein, negatively regulates the expression of CsANS, which encodes a key enzyme in Camellia sinensis catechin biosynthesis. Issue 4 (8th February 2019) - Zhang, Xueying; Jiang, Xiaolan; He, Yuqing; Li, Linying; Xu, Ping; Sun, Zongtao; Li, Junmin; Xu, Jiming; Xia, Tao; Hong, Gaojie
Abstract : Tea ( Camellia sinensis ) is an important cash crop that is beneficial to human health because of its remarkable content of catechins. The biosynthesis of catechins follows the flavonoid pathway, which is highly branched. Among the enzymes involved in catechin biosynthesis, ANTHOCYANIDIN SYNTHASE (CsANS) functions at a branch point and play a critical role. Our previous work has showed that the gene encoding CsANS is regulated by light signals; however, the molecular mechanism behind remains unclear. Here, we cloned a full‐length CsANS promoter and found that it contained a cis ‐element recognized by Arabidopsis thaliana HOMEOBOX2 (AtHB2). AtHB2 constitutes one of the class II HOMEODOMAIN‐LEUCINE ZIPPER (HD‐ZIP) proteins, which accumulate in the dark and mediate the shade avoidance response in most angiosperms. To analyze the transcription of CsANS in vivo, β‐glucuronidase and luciferase reporter genes driven by the obtained promoter were introduced into A. thaliana and Nicotiana attenuata, respectively. In both expression systems there were indications that the A. thaliana PRODUCTION OF ANTHOCYANIN PIGMENT1 (AtPAP1), a MYB transcription factor of flavonoid biosynthesis, increased the activity of the CsANS promoter, while AtHB2 could significantly undermine the effect of AtPAP1. Yeast two‐hybrid and bimolecular fluorescence complementation assays showed that AtHB2 interacted with the A. thaliana TRANSPARENT TESTA GLABRA 1 (AtTTG1). A yeast three‐hybrid assay further suggested that AtHB2 represses the expression of CsANS and regulates its response to light signals through competitive interactions with AtTTG1. These results show that HD‐ZIP II proteins participate in light regulation of flavonoid biosynthesis.